Toplotne izgube v tla pri stavbah glede na standard SIST EN ISO 13370 - poenostavljena metoda izračuna - Černe, Boštjan (Strojniški vestnik, 2001)
Heat losses from buildings through contact, with the ground, especially in the case of large buildings, have a strong influence on energy demand. Various methods for calculating these heat losses are available, including one method that is defined by the SIST EN ISO 13370 standard. Due of the complexity of this method we have developed a method that is presented in this paper. Using our method we have calculated weighting factors for buildings with and without basements with a variety of thermal transmittances of structures in the contact between the building and the ground. Also the number of influential parameters used in SIST EN ISO 13370 is reduced. Our simplified method is particularly appropriate for use in the process of designing the thermal insulation of buildings and determining the specific heat losses from buildings.
Keywords: zaščita toplotna; zaščita zgradb; prenos toplote; metode izračunavanja; toplotna zaščita; toplotne izgube; tlaki